Вплив англійської суднобудівної школи на формування морської сили на Чорному морі в першій половині XIX ст. - Рижева, Н.О. (Історичний архів. Наукові студії, 2015)
У статті розглядається стан Чорноморського флоту і суднобудування першої половини XIX ст. в безпосередній залежності від тих пріоритетів, які ставила Російська імперія на Півдні України. Головним завданням у цей час стає реалізація планів розширення територій за допомогою військово-морських сил.
Зіставлення наявних джерел дозволило автору зробити висновок, що на загальні процеси створення боєздатного флоту на Півдні України перш за все впливали провідні тенденції розвитку англійської суднобудівної школи. Її досягнення постійно вивчалися головними командирами Чорноморського флоту і портів. Інформація про новітні досягнення англійської кораблебудування досить швидко ставала відома на Півдні. У 20–40 рр. XIX ст., Для отримання навичок практичного кораблебудування, в Портсмутським і Плімутську адміралтейства Англії систематично направлялися фахівці верфей Миколаєва та Севастополя. Корабельні інженери і морські офіцери після навчання або стажування в Англії прагнули застосовувати передові технології при будівництві кораблів Чорноморського флоту. В статье рассматривается состояние Черноморского флота и судостроения первой половины XIX в. в непосредственной зависимости от тех приоритетов, которые ставила Российская империя на Юге Украины.
Сопоставление имеющихся источников позволило автору сделать вывод, что на общие процессы создания боеспособного флота на Юге Украины основное влияние оказывали главные тенденции развития английской судостроительной школы. Ее достижения постоянно изучались главными командирами Черноморского флота и портов. Информация о новейших достижениях английского кораблестроения достаточно быстро становилась известна на Юге. В 20–40 гг. XIX в., для получения навыков практического кораблестроения, в Портсмутское и Плимутское адмиралтейства Англии систематически направлялись специалисты верфей Николаева и Севастополя. Корабельные инженеры и морские офицеры после учебы или стажировки в Англии стремились применять передовые технологии в процессе строительства кораблей Черноморского флота. In the first half of the XIX-th century conditions of the Black Sea fleet and shipbuilding were completely dependent on the Russian empire priorities in the South. The main task at this time is the realization of plans to expand the borders using naval forces.
Comparison of the available sources suggests that the overall process of creation of efficient fleet in the south of the Russian Empire is directly influenced by the major trends in the development of English shipbuilding school. Its achievements were constantly studied by the chief commanders of the Black Sea Fleet and ports. The practice of holistic implementation of the achievements of the English shipbuilding school in the creation of the naval forces of the South begins through initiatives of A. Greig. Alex Samuilovich, the son of Vice Admiral Samuel Greig, who, at the invitation of Katherine II moved from the British fleet to the Russian one. In 1816, A. Greig was appointed as chief commander of the Black Sea Fleet and ports. Under his leadership, shipbuilding method of sarvayera chief G. Seppings was introduced on South Admiralty. Laying of 120-gun ship «Warsaw» in the Nicholas Admiralty on March 30, 1832 on the south of Ukraine is the evidence of fundamental changes in shipbuilding. Vessel was created with the aid of drawings of the English 120-gun ship «Neptun».
The information about the latest achievements of the English ship fairly quickly became known in the South, due to the continuation of the traditions laid by A. Greig, followed by the new chief commander of the Black Sea Fleet and ports M. Lazarev. In 30–40s of XIX-th century, experts from shipyards of Nikolaev and Sevastopol were regularly sent to Portsmouth and Plymouth Admiralty of England to obtain practical skills in shipbuilding. According to the available sources, M. Lazarev followed innovation implementation model developed by W. Symonds. The evidence of practical implementation of innovations becomes the laying of 120-gun ship «Twelve Apostles» on October 4, 1838 in the St. Nicholas Admiralty. The creation of its drawings was carried out under the influence of the innovations in the English shipbuilding, which were directly studied by naval architects of the Black sea shipyards. Modern Ukrainian and Russian studies of basic technical elements ships – «Twelve Apostles» and «Queen» (Portsmouth Admiralty) led to the conclusion of their similarity.
Thus, inherited traditions of ongoing research of western shipbuilding experience in the south contributed to systemic understanding of all manifestations. After study or internship in England naval architects and officers sought to apply advanced technologies in the construction of the Black Sea Fleet.